2020
DOI: 10.31486/toj.19.0058
|View full text |Cite
|
Sign up to set email alerts
|

Gamer's Thrombosis: A Review of Published Reports

Abstract: Background: Thrombosis, well known as a condition of the elderly, is occurring in the otherwise healthy adolescent population. Immobility is a significant risk factor for venous thromboembolism (VTE), and adolescents who play video games are immobile for extended periods of time. Some are presenting with VTE. When other risk factors such as obesity are present, the risk of VTE formation increases. We provide a review of published case reports regarding gaming and thrombosis. Methods: We searched PubMed, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Indeed, water retention can be a consequence of that, measured by bioelectrical impedance and reduced by wearing compression stockings [ 88 ]. Deep venous thrombosis is a rare but devastating consequence of that, as gaming has been linked to an hypercoagulability state [ 89 , 90 ]: a prompt diagnosis is crucial when a clinical suspicious raises, with compression ultrasound as a key diagnostic exam [ 91 ].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Indeed, water retention can be a consequence of that, measured by bioelectrical impedance and reduced by wearing compression stockings [ 88 ]. Deep venous thrombosis is a rare but devastating consequence of that, as gaming has been linked to an hypercoagulability state [ 89 , 90 ]: a prompt diagnosis is crucial when a clinical suspicious raises, with compression ultrasound as a key diagnostic exam [ 91 ].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Chronic systemic pathological conditions of the vascular system are mostly found in PEG subjects who are younger than 35 years old as compared with those older than 35 years old [24]. Stroke is a thromboembolic event which targets large and small vessels in the brain [5,25,26] and is often associated with pre-existing chronic systemic conditions such as general inflammation and cardiometabolic diseases, and can depend on previous thrombosis [24,27]. Lower limb thrombosis is quite common in Esports players, to the point of minting the term "e-thrombosis" [27].…”
Section: Resultsmentioning
confidence: 99%
“…Stroke is a thromboembolic event which targets large and small vessels in the brain [5,25,26] and is often associated with pre-existing chronic systemic conditions such as general inflammation and cardiometabolic diseases, and can depend on previous thrombosis [24,27]. Lower limb thrombosis is quite common in Esports players, to the point of minting the term "e-thrombosis" [27]. Thrombosis, however, can also be fatal in young subjects [28].…”
Section: Resultsmentioning
confidence: 99%
“…A lack of deep vein thrombosis on our workup does not exclude venous thromboembolism; studies have shown less than 50% of patients with proven pulmonary embolism have deep vein thrombosis [ 10 ], suggesting that a source of embolism is often not found. Among the teenagers, sedentary lifestyle, especially when associated with video gaming, has been identified as a modifiable risk factor for venous thromboembolism and reported in multiple case reports [ 11 , 12 ]. Our case demonstrates that the pandemic has had far-reaching effects, possibly leading to an increased stroke risk among the young due to a sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 99%